Suppression of age-related macular degeneration-like pathology by c-Jun N-terminal kinase inhibitor IQ-1S - Zhdankina, Anna A.; Tikhonov, Dmitry I.; Logvinov, Sergey V.; Plotnikov, Mark B.; Khlebnikov, Andrei I.; Kolosova, Natalia G. (Biomedicines)
Age-related macular degeneration (AMD) is the leading cause of irreversible visual impairment worldwide. The development of AMD is associated with inflammation, oxidative stress, and progressive proteostasis imbalance, in the regulation of which c-Jun N-terminal kinases (JNK) play a crucial role. JNK inhibition is discussed as an alternative way for prevention and treatment of AMD and other neurodegenerative diseases. Here we assess the retinoprotective potential of the recently synthesized JNK inhibitor 11H-indeno[1,2-b]quinoxalin-11-one oxime sodium salt (IQ-1S) using senescence-accelerated OXYS rats as a model of AMD. The treatment with IQ-1S (50 mg/kg body weight intragastric) during the period of active disease development (from 4.5 to 6 months of age) improved some (but not all) histological abnormalities associated with retinopathy. IQ-1S improved blood circulation, increased the functional activity of the retinal pigment epithelium, reduced the VEGF expression in the endothelial cells, and increased the expression of PEDF in the neuroretina. The result was a decrease in the degeneration of photoreceptors and neurons of the inner layers. IQ-1S significantly improved the retinal ultrastructure and increased the number of mitochondria, which were significantly reduced in the neuroretina of OXYS rats compared to Wistar rats. It seems probable that using IQ-1S can be a good prophylactic strategy to treat AMD.